2018
DOI: 10.1016/j.juro.2018.06.077
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model Using Machine Learning Algorithm for Assessing Stone-Free Status after Single Session Shock Wave Lithotripsy to Treat Ureteral Stones

Abstract: We applied a machine learning algorithm, a subfield of artificial intelligence, to predict the outcome after single session shock wave lithotripsy for ureteral stones. A 92.29% accurate decision model was developed with 15 factors and an average ROC AUC of 0.951.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 17 publications
0
24
1
1
Order By: Relevance
“…Our previous study on SWL also found that CTTA, a quantitative analysis method, may be useful in improving medical decision-making on ESWL patients ( 9 ). Similarly, several pieces of research showed that establishing a prediction model utilizing radiomics or machine learning may contribute to a better predictive efficacy for pre-operative estimation of PCNL or SWL outcomes ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study on SWL also found that CTTA, a quantitative analysis method, may be useful in improving medical decision-making on ESWL patients ( 9 ). Similarly, several pieces of research showed that establishing a prediction model utilizing radiomics or machine learning may contribute to a better predictive efficacy for pre-operative estimation of PCNL or SWL outcomes ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, this new methodology, named radiomics, has been proven to be capable of influencing and altering the diagnosis and treatment strategies in the field of tumors (10,11). Moreover, several investigations showed that predictive model based on radiomics or machine learning can better predict the post-operative outcome of certain surgical treatments (PCNL or SWL) (12,13). It is important to develop a novel predictive model for fURS that combines radiomics features and clinical indicators, particularly for the lower renal stones.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have evaluated different risk factors for failure of SWL on ureteric stones. Large stone size, HAV as measured in HU, high SSD and the presence of ureteric stents were reported as risk factors 11,14–17 . SW rate is another important factor with better stone fragmentation and better renal safety profile on slowing the rate down to 30–60 SW/min rather than 90–150 SW/min 18–20 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients aged between 18 and 80 years with single LPS of 1.5-3.5 cm were included in this study. Stone volume were calculated using the equation: length × width × height × π/6 [15]. Exclusion criteria are as follows: patients with renal malignancy, ectopic kidney, transplanted kidney stone, spongy kidney, polycystic kidney and uncontrolled pyonephrosis.…”
Section: Methodsmentioning
confidence: 99%